PENINGKATAN HASIL BELAJAR PPKn TENTANG HAKEKAT HUKUM DAN KELEMBAGAAN HAM DENGAN MEDIA PROBLEM CARD - Sumarwoto Sumarwoto (Program Pascasarjana Universitas Islam Darul `Ulum Lamongan, 2019)
: In the PPKn daily test on the Nature of Law and Human Rights Institutions, grade VII-C students of SMP Negeri 1 Pule Trenggalek received a very low class average score of 62.6 and classical learning completeness reached 46.7%. This shows that there are 14 students out of 30 students who have finished learning. This means that only 14 out of 30 students have achieved mastery learning. From the discussion with peers, it was found that the PPKn learning in class VII had been taking place only by using the lecture method without being accompanied by other methods that could involve students in learning. The teacher also does not use learning media that can concrete the material. So through this action research, the researcher wants to improve the learning outcomes of PPKn about the Nature of Law and Human Rights Institutions by applying a problem-based learning approach combined with problem card media. Research conducted by researchers is in the form of action research (action research). Based on the research that has been done, it is concluded that the application of the problem-based learning approach combined with the problem card media can improve the learning outcomes of PPKn about the Nature of Law and Human Rights Institutions. In the first learning cycle, the students' average learning achievement was 72 and classical learning completeness reached 70%. This shows that there are 21 students out of 30 students who have finished learning. In the second learning cycle, the average student achievement was 78.8 and classical learning completeness was 90%. This shows that there are 27 students out of 30 students who have finished learning. The application of a problem-based learning approach combined with problem card media in PPKn learning about the Nature of Law and Human Rights Institutions, begins with assigning students the task of observing snippets of news about law and human rights institutions that are broadcast by the teacher in front of the class. In the next lesson, students are given the task of group students to make clippings about human rights law and institutions.